Resurgent Islam and the politics of identity - Mazrui, Ali AlʼAmin (Cambridge Scholars Publishing, 2014)
One of the most important functions of religion is to serve as a basis of identity. This collection of essays by Ali A. Mazrui, a distinguished scholar of Islam, discusses how Islam differentiates Muslims from non-Muslims and affects how Muslims view each other. These essays delve into the complexities of Muslim identity and stratification, and provide contributions to key debates on modern Islamic political ideology. These essays will be of interest to readers engaged with Islam, religion, culture, comparative politics and international relations.